DNA methyltransferase 3 beta mediates the methylation of the microRNA-34a promoter and enhances chondrocyte viability in osteoarthritis - Shouliang Xiong (Taylor & Francis Group, 2021)
Osteoarthritis (OA) is characterized by destruction of articular cartilage with an imbalance between synthesis and degradation of extracellular matrix (ECM). In the current study, we explored the role of microRNA-34a (miR-34a) and the behind epigenetic mechanism in the degradation of ECM in OA. Using miRNA-based microarray analysis, we found that miR-34a was overexpressed in cartilage tissues of OA patients relative to patients with acute traumatic amputations. Moreover, its expression was positively correlated with the ECM degradation and inflammation. Mechanistically, miR-34a targeted MCL1, and possible target genes of miR-34a were enriched in the PI3K/AKT pathway. Furthermore, DNMT3B inhibited miR-34a by promoting miR-34a methylation. Functional experiments using CCK-8, flow cytometry, Safranin O staining, RT-qPCR, ELISA, Western blot, and HE staining revealed that miR-34a inhibitor suppressed ECM degradation and inflammatory response of chondrocytes and cartilage tissues. By contrast, downregulation of DNMT3B and MCL1 reversed the repressive effects of miR-34a inhibitor in vitro and in vivo. Altogether, our findings establish that silencing of miR-34a by DNMT3B could effectively reduce chondrocyte ECM degradation and inflammatory response in mice by targeting MCL1 and mediating the downstream PI3K/AKT pathway. This present study revealed that miR-34a knockdown might develop a novel intervention for OA treatment.